Harnessing Technology to Elevate Nursing Performance: A Strategic Approach for the Philippines - Sandigan, Nurnisa; Muhaymin, Armaida; Regidor, Marivic; Vilbar, Jhon May Lou; Ann Marie, Ann Marie; Tuscano-Volante, Ma. Cristine; Viernes, Marjorie Angeline; Sabdani, Tarwida; Tolentino, Diane Sheryll; Trocino, Jonathan (JPAIR Multidisciplinary Research, 2025)
This paper examines the impact of technology on nursing performance, specifically how technology can be incorporated into performance management in nursing. The research focuses on integrating Electronic Health Records (EHR), telehealth, mobile health applications (mHealth), and patient monitoring systems within the Philippine nursing environment. The study explores the association between the diffusion of these technology-enhanced healthcare tools and performance results through mixed methods—quantitative questionnaires and qualitative interviews. Participants included Bachelor of Nursing (BN) and Registered Nursing (RN) professionals with varying years of experience in different healthcare settings. Results indicate that EHR and telehealth are widely adopted and enhance the effectiveness of nursing practice. However, barriers such as inadequate training, poor implementation, and resistance to change hinder full integration into daily nursing routines. The study emphasizes that increasing the adoption of technological tools requires continuous training, leadership support, and strategic planning to overcome barriers. In conclusion, this paper underscores the importance of strategic planning in implementing technology within nursing to enable financial, technical, and professional readiness for change.